The assistance of e-dictionaries in learning English vocabulary to Indonesian EFL students - Tgk Maya Silviyanti; Yunisrina Qismullah Yusuf; Lia Cahya Ningrum; Martin Kustati (Journal of English Language Teaching Innovations and Materials (Jeltim), 2022)
This research investigated EFL Indonesian students' perception of using e-dictionaries in learning English. The subjects were 50 students still studying at a university in Banda Aceh, Indonesia. They completed a questionnaire, and ten were selected to be further interviewed. The questionnaire and interview questions were developed from several theories proposed by experts. The results of the study showed that the students had a positive attitude toward the use of e-dictionaries. Although e-dictionaries provided some benefits for students’ language learning, especially in vocabulary, such as ease of use, time, and place, the students also faced some difficulties using them. These included incomplete information on the definitions offered for words searched, uncomfortable and constant pop-up advertisements on the apps, cost and internet quota, and finally, eye health issues where students could not read their smartphone screen for some time duration. It is hoped that as the dominance of digital technology increases, more applications in the future can resolve these problems to better assist students in language learning.